MAP OF THE EARTH MASSES - ROLE IN THE INVESTMENT PROJECT: MAP OF THE EARTH MASSES - ROLE IN THE INVESTMENT PROJECT - Ivanov, Ivan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
Map of the earth masses shows the essence of the vertical planning project by visualizing the anticipated displacement of the land masses within the boundaries of the property. It is the official document through which the designer can determine the amount of land masses for the purpose of their valuation [5]. The article examines the role of the cartogram and modern practices regarding its creation and use in the investment process.